Registration of 'YZ05‐51' Sugarcane. Issue 2 (4th February 2015) - Zhao, Peifang; Liu, Jiayong; Yang, Kun; Xia, Hongming; Wu, Caiwen; Chen, Xuekuan; Zhao, Jun; Yang, Hongchang; Li, Jun; Zan, Fenggang; Wu, Zhuandi; Yao, Li; et al.
Abstract : 'YZ05‐51' (Reg. No. CV‐161, PI 673444) sugarcane (a complex hybrid of Saccharum spp.) was developed through cooperative research conducted by the Yunnan Sugarcane Research Institute (YSRI) of Yunnan Academy of Agricultural Sciences, and Yunnan Yunzhe Technology Development Co. Ltd. It was released to growers in mainland China on 1 Aug. 2013. YZ05‐51 was selected from the cross Yacheng 90‐56 × 'ROC 23' planned by YSRI and crossed at Yacheng Sugarcane Breeding Station (YSBS) of the Guangzhou Sugar Industry Research Institute, Yacheng, Hainan Province of mainland China in January 2005. The female parent (Yacheng 90‐56) is an advanced clone developed by YSBS. The male parent (ROC23) is a cultivar developed by the Taiwan Sugar Research Institute. YZ05‐51 was selected from a five‐stage selection program in YSRI and tested in the eighth China Regional Trial for Sugarcane Varieties at 14 locations in mainland China for 2 yr. YZ05‐51 was released by the China Committee of Sugarcane Variety Release because of its higher cane yield compared with ROC16 and ROC22 (two reference cultivars) (7.1 and 1.1%, respectively), its higher sugar yield compared with ROC16 and ROC22 (10.6 and 2.7%, respectively), and its resistance to drought, high resistance to smut (caused by Ustilago scitaminea H. & P. Sydow), and moderate resistance to mosaic ( Sorghum mosaic virus and Sugarcane mosaic virus ).